2020
DOI: 10.15407/itm2020.01.106
|View full text |Cite
|
Sign up to set email alerts
|

Study of the dynamics of freight cars with radial-type trucks

Abstract: At present, a topical problem for the Ukrainian railways is a reduction of freight car and track structure maintenance and repair cost. An increase in train mass and speed significantly increases vehicle and track wear due to increased wheel-rail interaction forces. A way to reduce wheel-rail wear and interaction forces in curves is to use devices that align the wheelsets in a radial orientation. The aim of this work was to analyze the effect of the design features of freight-car trucks associated with the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The work [6] involved the simulating the movement of freight wagons with various bogie design configurations along curved sections of the track. The analysis of the results obtained showed that the use of devices that ensure the radial installation of wheelsets has a positive effect on the processes of interaction between wheels and rails.…”
Section: The Main Part 21 Analysis Of Research and Publicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The work [6] involved the simulating the movement of freight wagons with various bogie design configurations along curved sections of the track. The analysis of the results obtained showed that the use of devices that ensure the radial installation of wheelsets has a positive effect on the processes of interaction between wheels and rails.…”
Section: The Main Part 21 Analysis Of Research and Publicationsmentioning
confidence: 99%
“…Research in works [1][2][3][4][5][6] and works [7][8][9][10] are different. In works [1][2][3][4][5][6], the dynamics of rolling stock and the stability of its movement have been extensively studied, accompanied by proposed approaches for preventing railway accidents.…”
Section: The Main Part 21 Analysis Of Research and Publicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study into the dynamics of freight cars equipped with devices for providing the radial installation of wheelsets is reported in work [10]. The authors modeled the movement of freight cars with various variants of bogie designs, including 18-100, along the curved sections of the track.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Our review of the scientific literature [1][2][3][4][5][6][7][8][9][10][11] allows us to conclude that the issue of prolonging the service life of cars, including a tank car, implying the use of Y25 bogies has not yet been covered. This necessitates appropriate research in the specified area.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%